An Assessment of Non-Timber Forest Products in Siddhababa Community Forest, Gulmi, Nepal - Bhandari, Samir; KC, Jyoti (Amrit Journal, 2024)
NTFPs (Non-Timber Forest Products) include all biological materials, excluding timber, derived from forests, pasturelands, other man-made and wild habitats which have socio-cultural, economic and other livelihood significance. The list of the NTFPs species found in SCF (Siddhababa Community Forest) was documented, the status of the NTFPs in the area was observed and the economic contribution of NTFP in the livelihood of community forest user group was studied. The systematic random sampling method was used for vegetation sampling. A total of 113 vascular plant species were documented from the study area among which 85 species were identified as potentially useful species (NTFPs). According to life form categories, among total NTFP species, 36 species (42.35 %) belong to herbs and grasses, followed by 33 species (38.82 %) tree and 16 species (18.82 %) shrub. Local people cultivated Amleeso (Thysanolaena maxima), Bans (Dendrocalamus hamiltonii), Tejpat (Cinnamomum tamala) and Timur (Zanthoxylum armatum). The status of the NTFPs suggest that western tropical regions of Nepal is suitable for large-scale production of the NTFPs in a commercial way benefiting local people and the economic development of the country.